Genome-wide identification and characterization of the Brassinazole-resistant gene family and associated responses to osmotic stress in Avena sativa - Xu, Shirui; Wei, Zihao; Ma, Mingchuan; Zhang, Lijun; Liu, Zhang; Liu, Longlong (Frontiers in Plant Science, 2025)
BackgroundThe Brassinazole-resistant (BZR) family of transcription factors acts as key regulators in brassinosteroid (BR) signaling, influencing plant growth, development, biotic and abiotic stresses. However, systematic analysis of the BZR genes in oat has not been conducted. Moreover, little is known about their functions in osmotic stress, which is a major abiotic stress affecting oat production.MethodsIn this study, we performed a genome-wide analysis of the BZR gene family in oat. Their chromosome locations, gene structures, phylogenetic relationships, conserved domains, promoter cis-elements, and gene duplication events were analyzed. Furthermore, the expression patterns of BZR genes under osmotic stress were characterized, and the subcellular localization of AsBZR12 was investigated in Nicotiana benthamiana.Results and discussionIn this study, we mapped 14 members of the BZR gene family across 12 oat chromosomes, and classified them into three groups based on phylogenetic analysis. The BZR proteins displayed group-specific patterns in their exon-intron structures and conserved motifs. Furthermore, cis-acting element analysis revealed that AsBZR genes are primarily involved in phytohormone responses and environmental stress adaptation. Examination of gene duplication revealed that segmental duplications drove the expansion of the BZR gene family in the oat genome, with evidence of strong purifying selection pressure during evolutionary development. The qRT-PCR analysis demonstrated varied expression patterns among AsBZR members. Specifically, AsBZR12 was significantly upregulated in roots, stems, and leaves, with nuclear localization. In summary, our study provides a comprehensive analysis of the AsBZR genes and characterizes their expression patterns under osmotic stress conditions, thereby identifying potential candidate genes for future research. This research provides comprehensive insights into BZR gene structure and evolution, establishing a foundation for understanding their osmotic stress responses in oat.